PERFORMANCE EVALUATION OF SENTUL GRAY CHICKEN AND THEIR ASSOCIATION WITH TLR1A GENE POLYMORPHISM - Suciati, Bella Permata (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The study examined the association between TLR1A gene polymorphism in exon 4 and the performance of Gray Sentul chickens. Conducted at the Jatiwangi Poultry Breeding Development Center. DNA from 30 males and 30 females was analyzed using PCR and sequencing to identify Single Nucleotide Polymorphism (SNPs). Data processing employed BioEdit and MEGA 11. Results revealed five mutations in males (g.775T>C, g.844 T>A, g.858C>T, g.983C>T, and g.1163G>A) and three in females (g.721G>A, g.983C>T and g.1163G>A). Males showed higher body weights, with optimal growth at 1–2 months. Peak egg production occurred at 41 weeks (HDP 44.97%), and the highest egg weight (46.93 g) at 55 weeks. Specific SNPs associated with performance traits include g.775T>C for body weight in males, g.1163G>A for body weight in females and egg production, and g.721G>A and g.983C>T for egg weight. This study concludes that the TLR1A gene can be used as a genetic marker to improve the performance of grey Sentul chickens.